2022
DOI: 10.3389/fcimb.2022.884793
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Antibiofilm Efficacy of Paeonol Treatment Against Biofilms Comprising Candida albicans and/or Cryptococcus neoformans

Abstract: Fungal populations are commonly found in natural environments and present enormous health care challenges, due to increased resistance to antifungal agents. Paeonol exhibits antifungal activities; nevertheless, the antifungal and antibiofilm activities of paeonol against Candida albicans and Cryptococcus neoformans remain largely unexplored. Here, we aimed to evaluate the antifungal and antibiofilm activities of paeonol against C. albicans and/or C. neoformans (i.e., against mono- or dual-species). The minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Glycerophospholipids are important components of cell membranes ( Sohlenkamp and Geiger, 2016 ; Qian et al, 2022 ). Previous studies have shown that glycerophospholipid metabolism plays an especially important role in the response to extracellular stress ( Lopalco et al, 2017 ; Zai et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids are important components of cell membranes ( Sohlenkamp and Geiger, 2016 ; Qian et al, 2022 ). Previous studies have shown that glycerophospholipid metabolism plays an especially important role in the response to extracellular stress ( Lopalco et al, 2017 ; Zai et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning of this study, no analyses of the transcriptome of duals-species communities could be found in the published literature. However, during the last year, several deep and substantial studies were published with two papers dedicated to communities of Candida albicans with different bacteria ( Staphylococcus aureus [ 38 ], Streptococcus mutans [ 39 ]), one manuscript about a fungal community of C. albicans and Cryptococcus neoformans [ 40 ], and one article focused on “coaggregated” Streptococcus gordonii and Fusobacterium nucleatum in mixed pellets, i.e., not in actual biofilm [ 39 ]. Interkingdom communities seem to be easier to analyze; however, in the streptococci-fusobacteria community, there was also a good correlation in results.…”
Section: Discussionmentioning
confidence: 99%
“…Short et al [ 38 ] and Lu [ 39 ] et al used 16S/18S rRNA genes for C. albicans / S. aureus [ 41 , 42 ] and S. gordonii / F. nucleatum, respectively. In case of C. albicans [ 39 ] and both C. albicans and C. neoformans [ 40 ], actin-encoding act1 gene was used as a reference. Interestingly, Lu and colleagues analyzed only the transcriptome of C. albicans and no data for S. mutans were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Its inhibitory effect is characterized by destroying bacterial cell membrane and blocking the biofilm structure formed on non‐biological surface (Zeng et al, 2022). Similarly, it can inhibit the formation of Candida albicans biofilm and play a therapeutic role on Candida albicans associated colitis (Ge et al, 2021; Pan et al, 2021; Qian et al, 2022). In addition, it also inhibited the expression of virulence factors of Pseudomonas aeruginosa to reduce bacterial virulence and reduce its damage to macrophages (Tang et al, 2022).…”
Section: The Latest Research Progress Of Paementioning
confidence: 99%